2007
DOI: 10.1111/j.1365-2958.2007.05962.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of heterologous and truncated RNase P proteins in Bacillus subtilis

Abstract: SummaryBacterial RNase P is composed of an RNA subunit and a single protein (encoded by the rnpB and rnpA genes respectively). The Bacillus subtilis rnpA knockdown strain d7 was used to screen for functional conservation among bacterial RNase P proteins from a representative spectrum of bacterial subphyla. We demonstrate conserved function of bacterial RNase P (RnpA) proteins despite low sequence conservation. Even rnpA genes from psychrophilic and thermophilic bacteria rescued growth of B. subtilis d7 bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…When divergences are further corrected to account for unseen substitutions, the sequences we tested exhibit pairwise divergences that range from 0.27 ( Proteus mirabilis rnpA ) to 1.72 ( S. oralis rnpA) amino acid substitutions per site. We thus confirm and extend the finding that endogenous bacterial RNase P proteins can be complemented in vivo by diverse phylogenetic heterologs [20], supporting tertiary structure and function conservation as defining features of the evolution of bacterial rnpA proteins.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…When divergences are further corrected to account for unseen substitutions, the sequences we tested exhibit pairwise divergences that range from 0.27 ( Proteus mirabilis rnpA ) to 1.72 ( S. oralis rnpA) amino acid substitutions per site. We thus confirm and extend the finding that endogenous bacterial RNase P proteins can be complemented in vivo by diverse phylogenetic heterologs [20], supporting tertiary structure and function conservation as defining features of the evolution of bacterial rnpA proteins.…”
Section: Resultssupporting
confidence: 83%
“…Comparative studies suggest that the tertiary structures of bacterial RNase P protein show remarkable conservation despite significant divergence in primary sequence [15], [16], [17], [18], [19]. As a result, highly divergent protein subunits taken from phylogenetically distant sources can still form a functional holoenzyme in vivo with the RNase P RNA subunit of Bacillus subtilis [17], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we addressed the question whether Hera and RnpA contact the same or overlapping binding sites on RNase P RNA in competition experiments (Figure 5). Cross-species complementation between different RNase P RNAs and RnpA proteins has been demonstrated in general (16,23,39,40), and specifically for T. thermophilus RNase P RNA and E. coli RnpA used here (41). Donor/acceptor-labeled Hera (50 pM) was incubated with 3 mM ADPNP and 50 nM T. thermophilus RNase P RNA, a concentration sufficient to induce the closure of the inter-domain cleft, and 200 nM E. coli RnpA (4-fold excess over Rnase P RNA) was added.…”
Section: Resultsmentioning
confidence: 80%
“…In fact, a genetic complementation approach revealed that both type A and M archaeal RPPs (expressed either individually or as binary complexes) were inadequate in rescuing the bacterial RPP defect in vivo (68). This result is consistent with our finding that an RNP made up of a bacterial RPR + archaeal POP5•RPP30 is ∼50-fold weaker than the bacterial RNase P holoenzyme (50).…”
Section: Discussionmentioning
confidence: 99%